Implementation of Teaching Module Development based on Artificial Intelligence (AI) Chat GPT - Zulfadewina; Ima Mulyawati; Siti Ithriyah; Septi Fitri Meilana (CV. Edujavare Publishing, 2026)
This study examines the implementation of the Artificial Intelligence (AI)-based teaching module ChatGPT at SDN Batu Ampar 02, focusing on teachers' challenges in utilizing AI technology due to limited technical knowledge and supporting facilities. The aim is to explore how ChatGPT can improve the quality and innovation of teaching modules. The study used a descriptive qualitative method with primary data through interviews, observations, and documentation, as well as secondary data from related literature. The results show that teachers are able to develop teaching modules that are more creative, relevant, and adaptive to students' needs. The implementation of AI also accelerated the module design process and strengthened teachers' digital literacy. These findings emphasize the importance of AI training and utilization in elementary education.